ACTH Regulation of Adrenal SR-B1 - Shen, Wen-Jun; Azhar, Salman; Kraemer, Fredric B. (Frontiers in Endocrinology, 2016)
The adrenal gland is one of the prominent sites for steroid hormone synthesis. Lipoprotein-derived cholesterol esters delivered via scavenger receptor, class B type 1 (SR-B1) constitute the dominant source of cholesterol for steroidogenesis, particularly in rodents. ACTH stimulates steroidogenesis through downstream actions on multiple components involved in steroidogenesis. Both acute and chronic ACTH treatment can modulate SR-B1 function including its transcription, its post transcriptional stability, its phosphorylation and dimerization status, as well as its interaction with other protein partners; all of which result in changes in the ability of SR-B1 to mediate HDL-cholesterol ester uptake and the supply of cholesterol for conversion to steroids. Here we provide a review of the recent findings on the regulation of adrenal SR-B1 function by ACTH.